The perception of UiTM Kelantan Branch students towards shariah compliant investment in Amanah Saham Nasional Berhad (ASNB) / Alia Najwa Anuar - Anuar, Alia Najwa (2024)
Perceptions related to sharia-compliant investments among university students are very important to improve investment practices that bring benefits to them in financial management. Investing in Amanah Saham Nasional Berhad (ASNB) is one of the companies that offered a variety of products to all eligible age groups. But unfortunately, this investment practice has not yet been utilized by students. This research examines the perception of 100 UiTM Kelantan Branch students regarding sharia-compliant investments in ASNB based on their level of financial literacy. Data was collected through a questionnaire regarding investments as a source of income for daily needs. The collected data was analyzed using descriptive analysis from the latest version of IBM SPSS Statistics software version 29 to find out the level of students' knowledge of compliant investments and investment product offerings at ASNB. As a result, the majority of 78 out of 100 students agreed that they are aware of and know clearly about shariah investments. While a total of 76 students chose Amanah Saham Bumiputera (ASB) as a shariah investment product. Next, among the influencing factors of sharia investment are wise financial planning, investment-related awareness, surrounding influences and last but not least, this investment must not practice elements that are forbidden in Islam. The research results also suggest that encouraging investment practices is very necessary for university students who are aware of the benefits of investing when they are involved in the investment field. The research is expected to contribute to the planning and management of financial literacy among university students.